Energi terbarukan dan emisi karbondioksida: Studi kasus Indonesia tahun 1990-2020 - Khoirunnisa, Triya Isma; Hidayah, Nur; Febrianti, Dewi Anisa (Journal of Economics Research and Policy Studies, 2024)
Renewable resources in Indonesia are abundant; however, the community and managers have not been able to utilize them optimally, resulting in a very low trend of renewable energy use in Indonesia. The country still relies on fossil fuels such as coal and petroleum, which are environmentally harmful due to the direct pollution caused by fossil fuel management. This dependency is difficult to change because of inadequate infrastructure and low costs. Therefore, this research aims to identify the factors that influence the use of renewable energy in Indonesia. The data used in this study are secondary data sourced from the World Bank website, covering the time series from 1990 to 2020 in Indonesia. The data, in numerical form, were processed using quantitative methods. The results of the data analysis indicate that the variables of fossil energy consumption, economic growth, and electricity consumption have a positive and significant effect on the use of renewable energy. In contrast, fossil energy consumption does not have a significant effect on the use of renewable energy in Indonesia. It can be concluded that the use of renewable energy can reduce the impact of carbon dioxide emissions resulting from mining, which directly affects the environment.